P93 Multi-modal simulation-based training improves confidence and competence in multi-disciplinary professionals managing acute non-invasive ventilation. (31st December 2017) - Spurr, L; Field, D; Chatwin, M; Pneh, E; Louro, I Sequeira; Hare, A
Abstract : Background: Non-invasive ventilation (NIV) is a ventilatory support mechanism used to manage respiratory failure in acute and chronic settings. The roles of members of the multi-disciplinary team (MDT) in managing NIV vary between hospitals. Provision and accessibility to supervision and training is also variable, and there is evidence that medical and nursing staff feel unprepared to deliver NIV in accordance with BTS guidelines. 1 We present results from a pilot course involving off-site multi-professional, multi-modal simulation-based NIV training, designed to directly improve patient safety by improving knowledge, and technical and non-technical skills of staff managing NIV. Methods: An interactive one-day course was developed to provide practical, multi-professional exposure to acute NIV management. This involved introductory lectures followed by low-fidelity simulation and part-task training workshops, prior to three multi-professional high-fidelity simulations (HFS) using HAL S3201 Patient Simulator. HFS scenarios were adapted from the European Respiratory Society (ERS) e-learning simulation programme. Each scenario involved different patient pathology and highlighted one or both of a) initiating NIV or b) recognising and managing NIV failure. Scenario participants acted in their normal professional roles. Simulations lasted 20 min, followed by semi-structured debrief involving participants and observers discussing technical and non-technical aspects of the scenario. A pre-post questionnaire was used to collect feedback on knowledge, skills and confidence in initiating and managing NIV. Results: Of 12 attendees (5 doctors; 3 nurses; 3 physiotherapists; 1 respiratory physiologist), 91% (n=11) managed NIV at least monthly. Pre-post questionnaires demonstrated significant improvement in confidence initiating NIV (p<0.05), ability to select initial NIV settings (p=0.01) and confidence in recognising patients experiencing NIV failure (p<0.01). There was no significant increase in knowledge of the principles of or indications for NIV which were predominantly presented and discussed in lecture based sessions. 100% (n=12) of attendees found the course either 'extremely useful' or 'useful', with 83% reporting HFS as either 'extremely useful' or 'useful'. Feedback predominantly highlighted 'simulation', 'scenarios' and 'interactivity' as the best aspects of the course. Conclusion: A combination of high- and low-fidelity simulation is an innovative and effective method of improving confidence and skills of the MDT in initiating and managing NIV. Interactivity and ability to demonstrate and discuss skills in real-time scenarios is seen as important component of the course by participants. Regular provision of this course will facilitate the development of effective multidisciplinary teamwork in the safe management of patients requiring NIV, and is in line with BTS guidance. Reference: 1. Plumb JOM, Juszczyszyn M, Mabeza G. Non-Invasive Ventilation (NIV) a study of junior doctor competence. The Open Medical Journal 2010;3:11–7.